Training Of Basic Techniques For Sepakraw Playing For Teachers Of Penjasorkes Basic School Of Padang Utara Sub-District - Padli Padli; Madri M; Zumroni Zumroni; yulifri yulifri (Jurnal Humanities Pengabdian Kepada Masyarakat, 2019)
Sports is one aspect of development that is gaining national attention in Indonesia, especially in efforts to improve nurseries, coaching, and achievement sports. Nurseries, coaching and improving the performance of sports not only in certain branches but also includes all sports activities in the community including Sepaktakraw sports. The sport of Sepaktakraw is very interesting, and it needs to be taken seriously because the game of Sepaktakraw is a very useful game and has developed a lot in Indonesia, especially in West Sumatra. This sport is popular because Sepaktakraw is full of beautiful acrobatic movements and is beneficial for bodily health. Nurseries, coaching activities towards achieving maximum achievement for this need to be held various preparations, especially the problem of coaches, athletes, organizations, infrastructure, and training programs, in order to improve the achievement to a higher level. In an effort to improve the quality of motion and improve the achievements of athletes in the game Sepak takraw, the technique is very closely related to the ability of movement, physical condition, tactics, and mental. One of the most basic places for coaching is in schools and through Physical Education learning. In connection with this, it is necessary to have training in basic techniques of sepaktakraw games for Penjasorkes teachers in Primary Schools in Padang Utara District, Padang City so that teachers can begin to do sepaktakraw training for students since elementary school.